Beach Cleanliness and Marine Debris Characteristics for Sustainable Coastal Tourism in Prigi Bay, Indonesia - Syamsuddin, Maura Fayza Dwinanda; Nevandra, Adinda Prameswari Aisyah; Yona, Defri; Yamindago, Ade; Sari, Syarifah Hikmah Julinda; Yanuar, Adi Tiya (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Tourist activity significantly impacts coastal ecosystems, often leading to increased marine debris pollution. This study examines the influence of tourism on beach cleanliness by analyzing marine debris composition, abundance, and Clean Coast Index (CCI) at four recreational beaches in Prigi Bay, Trenggalek, Indonesia (Cengkrong, Prigi, Karanggongso, and Mutiara). Sampling was conducted in March–April 2024, using a 5×5 m quadrat transect method placed at 20 m intervals along the shoreline in the backshore zone. The Mann-Whitney U test was applied to assess differences in debris accumulation between weekdays and weekends. Results indicated that plastic debris was the dominant type across all sites, with debris abundance slightly higher on weekends (54%) than weekdays (46%). Moreover, the mass of accumulated debris was significantly greater on weekends (1.93 items.m⁻², 8.86 g.m⁻²) than on weekdays (1.57 items.m⁻², 4.69 g.m⁻²), primarily due to an increase in larger debris items (10–100 cm), likely associated with tourism-related waste such as food packaging and recreational items. Despite these fluctuations, all beaches exhibited "extremely dirty" CCI scores (>20), indicating persistent pollution beyond tourism activity. Additional contributing factors may include inefficient waste management, fishing-related debris, and marine transport mechanisms. These findings underscore the urgent need for comprehensive waste management strategies, including source reduction, regular cleanups, improved waste disposal infrastructure, and public awareness campaigns, to mitigate long-term environmental and socio-economic impacts in Prigi Bay. Furthermore, integrating this measure into sustainable coastal tourism planning is crucial to balance recreational use with environmental preservation.